Menguji Kemampuan Membaca Al-Quran Calon Pemimpin Aceh dalam Prespektif Hukum Adat, Hukum Islam, dan Politik - Dinda Rachma Aditya; Inayatuzzahra Inayatuzzahra; Aristya Nadya Azhari; Salsa Arfa Nabillah; Cantika Asnanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Given Aceh's rich Islamic cultural traditions and foundations, reading the Quran is frequently regarded as a crucial prerequisite for future leaders in the area. The purpose of this study is to examine the significance of this skill in relation to politics, Islamic law, and customary law in Aceh. In order to provide a thorough knowledge of the problem from legal, social, cultural, and political perspectives, the study examines the perspectives of Acehnese society using empirical juridical research methods. It also reviews the pertinent legislation and the legal foundation. According to the research, the community expects leaders who comprehend and uphold Acehnese customary law and culture, and reading the Quran is considered a sign of good leadership abilities